2021
DOI: 10.1186/s12859-021-04194-5
|View full text |Cite|
|
Sign up to set email alerts
|

Moonlighting protein prediction using physico-chemical and evolutional properties via machine learning methods

Abstract: Background Moonlighting proteins (MPs) are a subclass of multifunctional proteins in which more than one independent or usually distinct function occurs in a single polypeptide chain. Identification of unknown cellular processes, understanding novel protein mechanisms, improving the prediction of protein functions, and gaining information about protein evolution are the main reasons to study MPs. They also play an important role in disease pathways and drug-target discovery. Since detecting MPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…We have worked with the concept one gene-one function, which is known to be inaccurate. It cannot be ruled out that proteins with low substrate specificity could replace the function of others (e.g., a specific methylase could be able to methylate non-specifically other substrates), while it is known that many proteins can be involved in more than one, sometimes unrelated, functions (moonlighting proteins; Shirafkan et al, 2021 ). In addition to experimental validation of genome reductions such as the one achieved with M. mycoides JCVI-syn3.0, a better delineation of what should be the minimal number of genes necessary to obtain a simplified but still efficient bacterial translational apparatus can be achieved by using machine-learning methods to detect replacements and moonlighting scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…We have worked with the concept one gene-one function, which is known to be inaccurate. It cannot be ruled out that proteins with low substrate specificity could replace the function of others (e.g., a specific methylase could be able to methylate non-specifically other substrates), while it is known that many proteins can be involved in more than one, sometimes unrelated, functions (moonlighting proteins; Shirafkan et al, 2021 ). In addition to experimental validation of genome reductions such as the one achieved with M. mycoides JCVI-syn3.0, a better delineation of what should be the minimal number of genes necessary to obtain a simplified but still efficient bacterial translational apparatus can be achieved by using machine-learning methods to detect replacements and moonlighting scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, it is difficult to identify and predict if a protein presents moonlight activity. However, bioinformatics approaches have been in development to aid in this process [25][26][27].…”
Section: Bacterial Moonlight Proteinsmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified that Dr. Javad Zahiri was not assigned as the co-corresponding author in the published article.…”
Section: Correction To: Bmc Bioinformatics (2021) 22:261 Https://doiorg/101186/s12859-021-04194-5mentioning
confidence: 99%